Formation of a Mechanism for Managing Investment Attraction in Free Economic Zones - Sheralieva Saida Azatovna (Research Parks Publishers, 2021)
This article is devoted to the establishment of the mechanism that would manage investment attraction in free economic zones of Uzbekistan as well as point out beneficial sides of FEZs and probable disadvantageous characteristics of Uzbekistan’s free economic zones. Moreover, this paper provides the examples of handling free economic zones in foreign countries and presents a number of statistical data to support the ideas.